2007
DOI: 10.1111/j.1538-7836.2007.02663.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, prospective clinical trial of recombinant factor VIIa for secondary prophylaxis in hemophilia patients with inhibitors

Abstract: To cite this article: Konkle BA, Ebbesen LS, Erhardtsen E, Bianco RP, Lissitchkov T, Rusen L, Serban MA. Randomized, prospective clinical trial of recombinant factor VIIa for secondary prophylaxis in hemophilia patients with inhibitors. J Thromb Haemost 2007; 5: 1904-13. Summary. Background: Hemophilic patients with factor VIII (FVIII) and FIX inhibitors suffer from frequent bleeding episodes and reduced quality of life. Objectives: To evaluate whether secondary prophylaxis with activated recombinant factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
380
2
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(399 citation statements)
references
References 32 publications
(49 reference statements)
8
380
2
9
Order By: Relevance
“…Regular prophylaxis is being considered also in patients with inhibitors, because a randomized study has shown that the prophylactic use of rFVIIa reduces the frequency of bleeding in patients with pre-existing joint damage [68]. The costs involved are exorbitant, but cost-effectiveness may be more favourable in small infants, particularly if less frequent dosing than that used so far to treat bleeding (for instance, once daily or every other day) is efficacious.…”
Section: What Next: Building On Strengthmentioning
confidence: 99%
“…Regular prophylaxis is being considered also in patients with inhibitors, because a randomized study has shown that the prophylactic use of rFVIIa reduces the frequency of bleeding in patients with pre-existing joint damage [68]. The costs involved are exorbitant, but cost-effectiveness may be more favourable in small infants, particularly if less frequent dosing than that used so far to treat bleeding (for instance, once daily or every other day) is efficacious.…”
Section: What Next: Building On Strengthmentioning
confidence: 99%
“…10 -12 Clinical experience from exploratory phase II trials, however, suggests that the hemostatic action of rFVIIa exceeds its predicted plasma half-life in patients subjected to prophylaxis. [13][14][15] Recent publications have highlighted the potential role of rFVIIa in prophylaxis of hemophilic patients with inhibitors. 14,16,17 Although the mechanisms of action of rFVIIa in the correction of active bleeding have been widely studied, those involved in the apparent long-lasting effects of rFVIIa for prophylactic treatment remain to be clarified.…”
mentioning
confidence: 99%
“…This mentorship was never just scientific; it has been academic, about how to be a woman in this environment, about networking and interacting with peers, and largely about life in general. [49], transfusion medicine, sickle cell disease, and evaluation of the impact of ageing-related health risks, particularly cardiovascular disease, on adults with hemophilia [50,51]. She has a long-standing drive to develop better testing for bleeding and clotting disorders, and is involved in clinical trials of new therapies for hemophilia and von Willebrand disease.…”
Section: Dr Kruse-jarres' Perspectivementioning
confidence: 99%
“…She has made numerous contributions to the field in the areas of von Willebrand factor modulation in pregnancy and the postpartum period, prevention of postpartum thrombosis, arising issues with hemophilia and aging [50], and the care of patients with hemophilia and inhibitors [49]. She has received federal funding from the NIH and the Centers for Disease Control and Prevention in many of these areas.…”
Section: Dr Sood's Perspectivementioning
confidence: 99%
See 1 more Smart Citation